Fundamental question determination procedures and project planning in PjBL at Muhammadiyah high schools - Iin Hindun; Sri Wahyuni; N. Nurwidodo (Universitas Muhammadiyah Malang, 2025)
Project-Based Learning (PjBL) is a learning model that aims to improve students' critical and creative thinking skills. However, the implementation of PjBL in the field still experiences obstacles, especially in the stages of determining basic questions and planning projects. This study aims to develop a procedural model for both stages and analyze teacher performance in implementing it. This study uses a development method (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the needs analysis show that teachers still do not understand the steps of PjBL and require comprehensive procedural guidance and adequate training. The model developed consists of systematic procedures in determining basic questions and planning projects. The results of the development are stated in a guidebook that is validated by learning experts. The implementation of the model is carried out through teacher training and trials on a small and large scale. Evaluation is carried out by testing the consistency of implementation. The results of the study show that this model can improve teacher understanding and performance in implementing PjBL effectively. Student responses to the developed model were also positive, indicating that this approach supports more meaningful learning.